KRITIK AL-QUR’AN TERHADAP MANUSIA (Kajian Tafsir Tematik Tentang Potensi Yang Ada Pada Diri Manusia) - marhaban marhaban (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2018)
Study of humans is extremely unique. It is appropriate that humans are said to be the noblest beings. Judging from the process of creation and its function, it has shown humans as beings chosen by God. Humans have extraordinary advantages. That advantage is endowed with reason and potentials in human beings themselves. Humans can develop their talents and potential and are able to manage and manage the universe of God's creation as a mandate. Even so, as a weak servant of humanity is not spared from sin and error because it is caused by human pride in using the potential that exists in man himself, as an example of the pharaoh because the potential that exists in him makes him arrogant in this earth and claiming to be God. So that Allah criticizes many people in many of his words contained in the Qur'an.